The Estonian speculative real estate market: The boom and bust cycle - Francesca Medda; Luca Cocconcelli (European Regional Science Association (ERSA), 2010)
The economic growth of the Baltic Region after independence has largely been realised through numerous reforms and capital market liberalisation. The Estonian economy in the past two decades was highly leveraged and characterised by the increase in real estate prices. This market had the pattern of a bubble. Our objective in this work is to evaluate through standard econometric analyses the effects of the speculative trend in real estate prices in Tallinn. In particular, we examine the presence and development of speculative bubbles in the financial and real estate markets. The analysis is extended in order to evaluate how the Estonian land fiscal system failed to prevent the market distortion. We demonstrate in the conclusion that a more rigourous implementation of the Estonian land tax could have diminished the effects of the boom and bust dynamics in the real estate market in Estonia.
Keywords: 330